Diabetes reduces mesenchymal stem cells in fracture healing through a TNF alpha-mediated mechanism - Ko, Kang I.; Coimbra, Leila S. [UNESP]; Tian, Chen; Alblowi, Jazia; Kayal, Rayyan A.; Einhorn, Thomas A.; Gerstenfeld, Louis C.; Pignolo, Robert J.; Graves, Dana T. (Springer, 2015)
Diabetes interferes with bone formation and impairs fracture healing, an important complication in humans and animal models. The aim of this study was to examine the impact of diabetes on mesenchymal stem cells (MSCs) during fracture repair.Fracture of the long bones was induced in a streptozotocin-induced type 1 diabetic mouse model with or without insulin or a specific TNF alpha inhibitor, pegsunercept. MSCs were detected with cluster designation-271 (also known as p75 neurotrophin receptor) or stem cell antigen-1 (Sca-1) antibodies in areas of new endochondral bone formation in the calluses. MSC apoptosis was measured by TUNEL assay and proliferation was measured by Ki67 antibody. In vitro apoptosis and proliferation were examined in C3H10T1/2 and human-bone-marrow-derived MSCs following transfection with FOXO1 small interfering (si)RNA.Diabetes significantly increased TNF alpha levels and reduced MSC numbers in new bone area. MSC numbers were restored to normal levels with insulin or pegsunercept treatment. Inhibition of TNF alpha significantly reduced MSC loss by increasing MSC proliferation and decreasing MSC apoptosis in diabetic animals, but had no effect on MSCs in normoglycaemic animals. In vitro experiments established that TNF alpha alone was sufficient to induce apoptosis and inhibit proliferation of MSCs. Furthermore, silencing forkhead box protein O1 (FOXO1) prevented TNF alpha-induced MSC apoptosis and reduced proliferation by regulating apoptotic and cell cycle genes.Diabetes-enhanced TNF alpha significantly reduced MSC numbers in new bone areas during fracture healing. Mechanistically, diabetes-enhanced TNF alpha reduced MSC proliferation and increased MSC apoptosis. Reducing the activity of TNF alpha in vivo may help to preserve endogenous MSCs and maximise regenerative potential in diabetic patients.
Keywords: Anti-TNF; Cytokine; Diabetes; Forkhead; Fracture healing; Hyperglycaemia; Inflammation; Mesenchymal stem cell; Tumour necrosis factor